The Effectiveness of Promotional Mix Elements in Achieving Customer Satisfaction in Saudi Mobile Telecommunications Services Companies - Aziza, Hossam (The Arab Journal of Administration, 2021)
Marketing of mobile telecommunications services companies requires effective marketing communication between the service provider and its customers, so the promotional activity of the company enables it to communicate with its potential customers using a set of tools in an effective way to create awareness and achieve its marketing objectives. Consumer satisfaction is critical in the services sector, there is an urgent need to evaluate the effectiveness of the promotional mix elements and their impact on customer satisfaction so that marketers in mobile telecommunications services companies can develop their marketing strategies to maximize customer satisfaction. This research attempts to answer the main question: Are the promotional tools used by Saudi mobile telecommunications services companies effective to achieve the desired level of customer satisfaction? The importance of this research is to study the effectiveness of the promotional mix elements in achieving customer satisfaction with the mobile telecommunications services companies in Saudi Arabia, and showing the most important factors in achieving customer satisfaction, and possibility of marketing management of these companies can benefit from the research findings and recommendations to help design their promotional strategies that achieve customer satisfaction and thus achieve their marketing objectives in this vital sector. The main objective of the study is to study the effectiveness of promotional mix elements in achieving customer satisfaction in Saudi Mobile telecommunications services companies. The research population was represented of the customers of mobile telecommunications companies in Riyadh, Saudi Arabia. The ICT sector includes three companies that provide mobile telecommunications services: STC, Mobily and Zain. Available sample of 384 individuals. The research found that the effectiveness of the promotional mix components used by mobile telecommunications services was medium. There is a statistically significant positive effect on the promotional mix elements used by Saudi mobile telecommunications services in customer satisfaction. There are also significant differences between STC’s customers, Mobily’s customers and Zain’s customers regarding their responses to the promotional mix used by these companies, as well as substantial differences in their satisfaction.